2001
DOI: 10.1161/01.atv.21.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Lifestyle Determinants of Postprandial Lipemia Differ From Those of Fasting Triglycerides

Abstract: Abstract-Despite the reported association of lipoprotein responses to a fatty meal with atherosclerosis, little is known about the determinants of these responses. Plasma triglyceride, retinyl palmitate, and apolipoprotein B-48 responses to a standardized fatty meal containing a vitamin A marker were measured in 602 Atherosclerosis Risk in Communities (ARIC) study participants. To focus on postprandial responses specifically, which have been reported to be related to atherosclerosis independently of fasting tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 43 publications
7
54
0
2
Order By: Relevance
“…Furthermore, the APOE3/2 genotype was associated with a greater variability in the postprandial responses. Fasting triacylglycerol concentration was associated with postprandial triacylglycerol response consistent with earlier reports in a population-based sample (Sharrett et al, 2001) and in subjects with type II diabetes (Reznik et al, 2002). It is suggested that dietary sucrose could increase synthesis and secretion of APOB (Abraham et al, 1994;Hellerstein, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the APOE3/2 genotype was associated with a greater variability in the postprandial responses. Fasting triacylglycerol concentration was associated with postprandial triacylglycerol response consistent with earlier reports in a population-based sample (Sharrett et al, 2001) and in subjects with type II diabetes (Reznik et al, 2002). It is suggested that dietary sucrose could increase synthesis and secretion of APOB (Abraham et al, 1994;Hellerstein, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…In that case, a similar standardized test meal is to be used in every subject. (Weintraub et al, 1988(Weintraub et al, , 1989Lopez-Miranda et al, 1997Patsch et al, 1992;Mekki et al, 1999;Minihane et al, 2000;Tiret et al, 2000;Sharrett et al, 2001;Robertson et al, 2002;Jackson et al, 2003;Harbis et al, 2004).…”
Section: Aim Of Postprandial Lipaemia Testsmentioning
confidence: 99%
“…Fasting parameters (triglyceridaemia, cholesterolaemia, glycaemia) can be moderately elevated but with absence of any drug therapy. Compared with healthy subjects who demonstrate wellregulated lipid homeostasis, these subjects can be especially sensitive to meal challenges (Patsch et al, 1983;Mekki et al, 1999;Sharrett et al, 2001;Finnegan et al, 2003).…”
Section: Subjects At Disease Risk or Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifestyle and diet are, therefore, the major determinants of the phenotypic expression of major changeable risk factors (systemic arterial hypertension, dyslipidemia and diabetes). A recent study 22 has emphasized that smoking and diet were the major risk factors responsible for postprandial hyperlipemia, which is known to be a condition associated with the atherosclerotic process. An improvement in these determinants is associated with better control of these risk factors and a reduction in the incidence of the coronary artery disease 23 .…”
Section: Discussionmentioning
confidence: 99%